The swansong of the fascist octopus: creating effective change communications. Issue 4 (16th July 2018) - Hirsch, Peter
Abstract : Purpose: The purpose of this paper is to examine why corporations frequently do such a bad job in change communications and succumb to clichéd terminology when communicating change. Design/methodology/approach: The approach was to identify particularly egregious examples of poor communications and to identify some reasons why change communications seems so difficult for large corporations. Findings: Poor change communications has a number of sources. Chief of these is the failure to involve employees in the change process from the beginning and to acknowledge candidly that all change processes have losers as well as winners. Research limitations/implications: The views expressed in the paper are based on the author's own experience rather than extensively researched data. Practical implications: While poor change communications will always exist, leaders who understand the natural tendency to use obscure and clichéd language in the field will be able to mitigate its effects. Social implications: With trust in corporations at all-time lows, one can believe that more effective change communications will help to restore some of the lost trust between capital and labor. Originality/value: While the clichéd corporate language is the frequent target of critics, there are few treatments of its connection with change communications.